International University Networks and Academic Mobility in Political Context: Six decades of cooperation between “Babeș-Bolyai” University in Cluj-Napoca and the University of Geneva (1919-1979) - Florin Nicolae Ardelean (Journal of Research in Higher Education, 2020)
The aim of this paper is to analyse academic mobility and other forms of scientific cooperation against a larger political background. The relations between “Babeș-Bolyai” University in Cluj-Napoca and the University of Geneva, between 1919 and 1979, were marked by radical political changes. The shifting international context had a particularly great impact on the Romanian institution, which made a difficult transition from a democratic to a totalitarian regime after World War II. In the first part of the paper, we identified contacts between the Romanian University in Cluj and the Swiss academic community during the interwar period (1919-1939). It was a favourable period for international scientific collaboration, when a “tradition” of cooperation between the universities of Cluj and Geneva was born. The second part of the paper is focused on the various forms of cooperation between the two institutions in the following decades (1939-1979), with a special emphasis on academic mobility. A significant moment was the signing of a cooperation convention in 1971. The information provided by official documents issued by the two universities during the following years reveals the numerous obstacles they faced in their efforts to implement the provisions of the convention.